KCCI's Role in South Korean Cultural Diplomacy in Indonesia During The 2019-2022 Covid-19 Pandemic - Andhika, Nibras; Amalia, Novi Rizka (UNIDA GONTOR, 2023)
South Korea is one of the countries that prioritize diplomacy techniques to build the integrity of its country, one of which is through cultural diplomacy. KCCI is a cultural center located in Indonesia that aims to introduce Korean culture. In this research, the author intends to find out the role of KCCI in developing its cultural diplomacy in Indonesia during the COVID-19 Pandemic by using qualitative data collection methods such as quoting from several journals and direct KCCI website data. The findings of this study, through the role of KCCI which optimizes online media Youtube, Facebook, and Instagram to promote Korean culture as a form of cultural diplomacy in Indonesia during the Covid Pandemic - 19. Besides the South Korean government which focuses on fighting the spread of the Corona virus, the existence of KCCI as a Korean cultural center during this pandemic is needed to promote Korean culture. Some of the activities it has carried out during this pandemic ranging from online to offline activities such as the Korean Food Carnival, several online cultural event sessions with the theme